2022
DOI: 10.3390/cells11050865
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of A-Type Lamin Targeting to Nuclear Ruptures Are Disrupted in LMNA- and BANF1-Associated Progerias

Abstract: Mutations in the genes LMNA and BANF1 can lead to accelerated aging syndromes called progeria. The protein products of these genes, A-type lamins and BAF, respectively, are nuclear envelope (NE) proteins that interact and participate in various cellular processes, including nuclear envelope rupture and repair. BAF localizes to sites of nuclear rupture and recruits NE-repair machinery, including the LEM-domain proteins, ESCRT-III complex, A-type lamins, and membranes. Here, we show that it is a mobile, nucleopl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 96 publications
1
17
0
Order By: Relevance
“…In the highly expressing cells, mEmerald-LA modestly accumulated at the rupture sites (∼1.2-fold enrichment 150 s after irradiation; Fig. 3, A–C ), in accordance with previous studies ( Denais et al, 2016 ; Sears and Roux, 2022 ; Young et al, 2020 ). Thus, the diffusible LA and LC in the nucleoplasm appear to be involved in the accumulation.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…In the highly expressing cells, mEmerald-LA modestly accumulated at the rupture sites (∼1.2-fold enrichment 150 s after irradiation; Fig. 3, A–C ), in accordance with previous studies ( Denais et al, 2016 ; Sears and Roux, 2022 ; Young et al, 2020 ). Thus, the diffusible LA and LC in the nucleoplasm appear to be involved in the accumulation.…”
Section: Resultssupporting
confidence: 92%
“…Next, we investigated the effect of the phosphorylation of LA/C at Ser 22 on accumulation at the rupture sites because previous studies have shown that this phosphorylation increases the nucleoplasmic pool ( Kochin et al, 2014 ) and is detected at the rupture sites ( Sears and Roux, 2022 ). To examine if the accumulating LC is phosphorylated, WT MEFs expressing sfGFP-DARPin-LA6 were laser-microirradiated, fixed within 10 min, and stained with an anti-phospho-Ser 22-LA/C antibody.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…NGPS remains poorly characterized compared to HGPS, and insights into the molecular mechanisms behind the disease have only recently started to emerge (14)(15)(16). Therefore, with the aim of identifying new genes and pathways relevant to NGPS, as well as potential targets for therapeutic avenues in the disease, we carried out a whole genome CRISPR/Cas9 arrayed microscopy screen in patient derived NGPS cells.…”
mentioning
confidence: 99%